High-frequency counter-flow plasma synthetic jet actuator and its application in suppression of supersonic flow separation. (January 2018) - Wang, Hongyu; Li, Jun; Jin, Di; Tang, Mengxiao; Wu, Yun; Xiao, Lianghua
Abstract: We come up with a control strategy for suppression of supersonic flow separation based on high-frequency Counter-flow Plasma Synthetic Jet Actuator (CPSJA). The main purpose of this investigation is to verify if its control authority can be enhanced by the jet/shock interaction. We use a blunt nose to generate a bow shock, a step on a flat plate to introduce a massive separation in a Mach 2 wind tunnel, and the CPSJA to generate Plasma Synthetic Jet (PSJ). In this study, pulsed capacitive discharge is provided for an array of CPSJAs, which makes the actuation (discharge) frequency f 1  = 1 kHz, f 2  = 2 kHz and f 3  = 3 kHz. We use the high-speed schlieren imaging and fast response pressure transducers as well as a numerical simulation to investigate the quiescent PSJ properties, the interaction between the jet and bow shock, and its disturbance effect on the downstream separated region. The schlieren images show that PSJ is characterized by a succession of vortex rings; the jet strength weakens with the increase of frequency. A 4.5 mN jet thrust is found for all the frequencies. The simulation results show that jet/shock interaction produces vorticity in the vortex ring of the jet, enhancing turbulent mixing in PSJ so that a great deal of momentum is produced into the flow. We found the downstream flow is significantly disturbed by the enhanced actuation. Actuation with frequency of f 2, f 3 which is close to the natural frequency f n of the separation bubble suppresses the separation with the upstream laminar boundary layer being periodically attenuated, which has a better control effect than f 1 . The control effect is sensitive to the position where PSJ interacts with the shear layer, but the amount of energy deposited in one pulse is not crucial in a separation reduction in the experiment. Highlights: A control strategy CPSJA for suppression of supersonic flow separation is proposed. The control authority is enhanced via jet/shock interaction. The downstream separation can be suppressed by the enhanced plasma synthetic jet.